New records of Encyrtidae (Hymenoptera: Chalcidoidea) from the Netherlands, with a description of new species - Japoshvili, George; Soethof, Rudy (Zootaxa, 2022)
As a result of our survey of parasitoid wasps, the number of encyrtid species known from the Netherlands increased from 106 to 123. Microterys nederlandicus Japoshvili sp. n. is described as new for science. Figures for all species identified during our survey are provided.